The Relationship between Dietary Acid Load with Kidney Function among Chronic Kidney Disease Patients: HUBUNGAN DIETARY ACID LOAD DENGAN FUNGSI GINJAL PADA PENDERITA GAGAL GINJAL KRONIS - Faza Yasira Rusdi; Mira Dewi; Cesilia Meti Dwiriani (Media Gizi Indonesia, 2023)
Chronic kidney disease (CKD) affects the structure and function of the kidneys. The burden of disease from CKD is expected to increase as the prevalence of CKD increases from year to year. The quality of the diet plays a role in the management and treatment of CKD. The diet quality of CKD patients is assessed using dietary acid load (DAL) which is estimated based on protein and potassium intake. A high score of DAL can lead to more rapid decline in renal function, rapid decline in GFR, and low-grade subclinical acidosis. This study was aimed to analyze the relationship between dietary acid load and kidney function in CKD patients with hemodialysis at the Bogor City Hospital. This study used a cross sectional design involving 50 subjects with CKD on hemodialysis. Data was collected by interview using a questionnaire for data characteristics and Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) for data intake. There was a significant relationship between DAL and eGFR, urea, and creatinine (p<0,05). The level of DAL plays an important role in the development and severity of CKD. Therefore, dietary recommendations for patients CKD on hemodialysis need to focus to the dietary acid load derived from foods and to the condition of hyperkalemia. Further research is expected to be carried out with an intervention, case control or cohort design, as well as using different equations in estimating DAL such as the net acid excretion (NAE), potential renal acid load (PRAL) equation.